2023
DOI: 10.1021/acs.est.3c04524
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Single-Cell Exposomics by Mass Spectrometry

Abstract: Single-cell exposomics, a revolutionary approach that investigates cell−environment interactions at cellular and subcellular levels, stands distinct from conventional bulk exposomics. Leveraging advancements in mass spectrometry, it provides a detailed perspective on cellular dynamics, interactions, and responses to environmental stimuli and their impacts on human health. This work delves into this innovative realm, highlighting the nuanced interplay between environmental stressors and biological responses at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Exposomics investigations are conducted through the application of omics-based technologies that identify biomarkers of exposure and responses to chemical and biological agents or radiation [97]. Recently, Gao (2023) showed that single-cell exposomics is a revolutionary approach that investigates the interactions between cell and environment stressors at cellular and subcellular level, especially based on spatial and high resolution mass spectrometry (MS) analysis [98]. Thus, recent advancements in single-cell technologies have enabled detection of RNA, by single-cell RNA sequencing (scRNA-seq) [99], proteins, by single-cell proteomics by MS, metabolites, by mass spectrometry imaging (MSI) or secondary ion mass spectrometry (SIMS), and xenobiotics, including drugs, by single-probe single-cell MS or capillary electrophoresis-laser-induced fluorescence, in individual cells, by time-of-flight MS (CyToF), contributing to a better understanding of mammary cell diversity [100] or demonstrating that distinct cell populations express xenobiotic metabolizing enzymes, which indicate variability in xenobiotic metabolism not only between organs, but also at a tissue and cell level [101].…”
Section: Bc Is An Ecological/environmental Disordermentioning
confidence: 99%
“…Exposomics investigations are conducted through the application of omics-based technologies that identify biomarkers of exposure and responses to chemical and biological agents or radiation [97]. Recently, Gao (2023) showed that single-cell exposomics is a revolutionary approach that investigates the interactions between cell and environment stressors at cellular and subcellular level, especially based on spatial and high resolution mass spectrometry (MS) analysis [98]. Thus, recent advancements in single-cell technologies have enabled detection of RNA, by single-cell RNA sequencing (scRNA-seq) [99], proteins, by single-cell proteomics by MS, metabolites, by mass spectrometry imaging (MSI) or secondary ion mass spectrometry (SIMS), and xenobiotics, including drugs, by single-probe single-cell MS or capillary electrophoresis-laser-induced fluorescence, in individual cells, by time-of-flight MS (CyToF), contributing to a better understanding of mammary cell diversity [100] or demonstrating that distinct cell populations express xenobiotic metabolizing enzymes, which indicate variability in xenobiotic metabolism not only between organs, but also at a tissue and cell level [101].…”
Section: Bc Is An Ecological/environmental Disordermentioning
confidence: 99%
“…These technologies offer unprecedented insights into the molecular mechanisms underpinning the biological responses to environmental exposures. By elucidating the complex interactions and mixture effects of various contaminants at a molecular level, omics approaches aid in developing more effective and targeted mitigation strategies . These technologies not only enhance our understanding of individual contaminants but also illuminate the broader picture of how mixtures of substances interact and impact biological systems.…”
mentioning
confidence: 99%